Periodicity in the length of 3'-poly(A) tails from native globin mRNA of rabbit. - Kelly, J M (1982)
Globin mRNA from rabbit reticulocytes was labelled at the 3'-end with [5'-32P]pCp by T4 RNA ligase. The 3'-poly(A) tail was released by digestion of mRNA with T1 ribonuclease and its size distribution determined by gel electrophoresis and autoradiography. The length of the 3'-poly(A) tails varied from about 15-150 residues, but the size distribution exhibited peaks in the abundance of poly(A) species at intervals of approx. 25 residues. This periodicity appears to reflect the manner in which proteins bind to the 3'-poly(A) tail. The function of such regular interactions may be to control mRNA breakdown in the cytoplasm.